STUDENTS’ TSUNAMI PREPAREDNESS LEVEL COMPARISON IN PANGANDARAN, INDONESIA - Marlyono, Setio Galih (Universitas Pendidikan Indonesia, 2019)
The spread of schools in disaster-prone areas increases the risk of students’ fatalities. Data on the level of preparedness between elementary, junior high and senior high school students is urgently needed to see appropriate approach for improving students’ preparedness. This study used descriptive method inwhich surveys was used as the data collection technique. Data consist of primary and secondary evidence. The data were analyzed using standard depiction of charters, LIPI and UNESCO parameters. The sample consisted of elementary, junior high, and senior high school students in Pangandaran District. Based on the results of t test, it was found that there are significant differences between the level of preparedness of elementary and junior high school students, there are significant differences between the preparedness of elementary and senior high school students, and there is no significant difference between the preparedness of junior and senior high school students. There is a fact that the the Ministry of Education and Culture of Republic of Indonesia and teachers are those contributing to the students’ preparedness level.